2014
DOI: 10.1039/c4tb00339j
|View full text |Cite
|
Sign up to set email alerts
|

In situ synthesis, characterization and in vitro studies of ciprofloxacin loaded hydroxyapatite nanoparticles for the treatment of osteomyelitis

Abstract: Bioactive materials in combination with antibiotics are widely developed for the treatment of osteomyelitis which play a dual role: as bone substitutes at the affected site and as local drug delivery systems for antibiotic delivery. In the present study, a series of ciprofloxacin loaded hydroxyapatite (HA) nanoparticles with sustained and prolonged release behavior has been synthesized by an in situ precipitation method. The amount of ciprofloxacin loaded on HA nanoparticles can be easily adjusted by changing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(54 citation statements)
references
References 51 publications
1
46
0
7
Order By: Relevance
“…The intensity of the peak at 3242 cm −1 decreased after the heat treatment of the sample at 800°C for 3 h [29,30]. Besides, the weak peaks observed at 1419 and 1326 cm −1 attributed to the absorption bands of -CO , 3 2 signifying the existence of carbonate ions due to atmospheric CO 2 [31,32] . A weak band noticed at 2140 cm −1 in all the samples was assigned to (ѵ 3 ) asymmetric stretching of carbonate -CO , 3 2 ion impurity [5].…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The intensity of the peak at 3242 cm −1 decreased after the heat treatment of the sample at 800°C for 3 h [29,30]. Besides, the weak peaks observed at 1419 and 1326 cm −1 attributed to the absorption bands of -CO , 3 2 signifying the existence of carbonate ions due to atmospheric CO 2 [31,32] . A weak band noticed at 2140 cm −1 in all the samples was assigned to (ѵ 3 ) asymmetric stretching of carbonate -CO , 3 2 ion impurity [5].…”
Section: Resultsmentioning
confidence: 95%
“…The XRD analysis shows that the HA nanorods fabricated using caffeine are highly crystalline in nature. A sharp, small peak noticed at 25.84 (2θ) indicates the (002) Miller's plane, which shows the nucleation of crystals initiated along the c-axis of the HA nanorods [32]. The existence of corresponding diffraction peaks at lattice planes (002), (211), (300) and (213) confirmed the presence of hydroxyapatite with a hexagonal phase structure, which matched with the standard (JCPDS No.9-0432).…”
Section: Xrd Analysismentioning
confidence: 99%
“…pH value of the medium increased for the samples C, F, and G up to 7 days due to the release of OHfrom the samples by dissolutions in the soaking medium. 43 EDX analysis showed that the mineral deposits that formed on samples were mainly composed of carbon (C), oxygen (O), calcium (Ca), phosphorous (P), and magnesium (Mg). 37,52 3.6 | Bioactivity Figure 9 shows the SEM images of the surface of compacted samples (disk) after soaking in SBF for 21 days.…”
Section: Dissolution Studymentioning
confidence: 99%
“…The bands observed at 875, 1424, and 1457 cm -1 correspond to B-type carbonate impurities and such carbonation was due to the reactive absorption of atmospheric carbon dioxide by the sample during sample preparation. [42][43][44] The band at 1642 cm -1 is attributed to the ν 2 bending mode of the adsorbed H 2 O molecules. The broad band extending from 2500 to 3600 cm -1 is attributed to the ν 3 and ν 1 stretching modes of the adsorbed H 2 O molecules.…”
Section: Fourier Transform-infrared Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation